Clinical Usefulness of Child-centered Task-oriented Training on Balance Ability in Cerebral Palsy - Lee, Byoung-Hee; Kim, Yumi (Journal of Physical Therapy Science, 2013)
[Purpose] This study was conducted in order to investigate the effects of child-centered task-oriented training on balance ability in patients with cerebral palsy. [Subjects] Twenty-six subjects with cerebral palsy were recruited. [Methods] This study applied a child-centered task-oriented training program to 26 subjects during a period of 15 weeks, with two 40-minute sessions per week. The Pediatric Berg Balance Scale (PBS) was used for measurement of the effect of child-centered task-oriented training. [Results] Balance ability showed a significant change after the intervention in age groups younger than nine, between 10 and 12, and older than 13. In addition, a significant difference in balance ability was observed in the spastic type, athetoid type, diplegia, and quadriplegia transport groups, including an independent walking group, a group of subjects who used walkers, and a group of subjects who used wheelchairs. [Conclusion] Although we suggest conduct of a follow-up study on child-centered task-oriented training, the results of this study showed improved balance ability in patients with cerebral palsy. Therefore, these results recommend a variety of applications in clinical trials of conservative therapeutic methods.